Suppression of early hematogenous dissemination of human breast cancer cells to bone marrow by retinoic acid-induced 2 - Werner, Stefan; Brors, Benedikt; Eils, Roland (Cancer discovery, 2015)
Regulatory pathways that drive early hematogenous dissemination of tumor cells are insufficiently defined. Here, we used the presence of disseminated tumor cells (DTC) in the bone marrow to define patients with early disseminated breast cancer and identified low retinoic acid-induced 2 (RAI2) expression to be significantly associated with DTC status. Low RAI2 expression was also shown to be an independent poor prognostic factor in 10 different cancer datasets. Depletion of RAI2 protein in luminal breast cancer cell lines resulted in dedifferentiation marked by downregulation of ERα, FOXA1, and GATA3, together with increased invasiveness and activation of AKT signaling. Functional analysis of the previously uncharacterized RAI2 protein revealed molecular interaction with CtBP transcriptional regulators and an overlapping function in controlling the expression of a number of key target genes involved in breast cancer. These results suggest that RAI2 is a new metastasis-associated protein that sustains differentiation of luminal breast epithelial cells. Significance: We identified downregulation of RAI2 as a novel metastasis-associated genetic alteration especially associated with early occurring bone metastasis in ERα-positive breast tumors. We specified the role of the RAI2 protein to function as a transcriptional regulator that controls the expression of several key regulators of breast epithelial integrity and cancer. Cancer Discov; 5(5); 506-19. ©2015 AACR. See related commentary by Esposito and Kang, p. 466 This article is highlighted in the In This Issue feature, p. 453